PEMBERDAYAAN PETANI SAYURAN: KASUS PETANI SAYURAN DI SULAWESI SELATAN - Lukman Hakim; Basita G. Sugihen (Jurnal Penyuluhan, 2007)
This study was focused on analyzing farmers’ empowerment and studying factors affecting group dynamic in relation with their business improvement. The objectives of this study were: (1) to identify factors that influence empowerment of crop farmer within groups, (2) the relation between group dynamics and productivity and, (3) the formulation of empowerment strategy through group approach. This study was conducted at two districts area: Gowa and Enrekang at South Sulawesi Province. Primary data were obtained from 240 respondents from members of group farmer who their business mostly cultivate vegetable. Quantitative analysis and qualitative-descriptive analysis were employed to explain the result of the research. Variabels used in the study were individual characteristics. The level of farmer empowerment within group is low, and factors that affect farmers’ empowerment within group are low (underdeveloped). These factors are empowerment pattern, level of personality, social environment, information access and level of farmers’ productivity. Development of elements of group dynamics in two locations shows low performance that means underdeveloped. The main constraints for developing group dynamics are lack of initiative and participation of group members to encourage group activities, and lack of cooperation and coordination of tasks within group. Individual characteristics include level of formal education, empowerment pattern, farmers’ personality, social environment and information access show significantly positive relationship with group dynamic. There are fourteen variabels which positively influence group dynamics. These variabels are empowerment pattern; level of farmers’ personality; social environment; and information access. Based on the relationship among variabels in the model of farmer development toward farmer’s productivity, it shows that variabels of working network (X2.2), self confident (X3.2), culture norms (X4.1), accurate information (X5.2), group objective (Y1.1) and group development (Y1.3) affect significantly of farmers’ productivity. This means these variables have significant role in promoting farmers’ productivity. Farmers’ productivity is still low and it should be developed through more diynamic activities.